Decolonizing Indigenous Histories : Exploring Prehistoric/Colonial Transitions in Archaeology - Frink, Liam, 1962-; Hart, Siobhan M., 1977-; Oland, Maxine, 1978- (Book collections on Project MUSE., 2012)
Decolonizing Indigenous Histories makes a vital contribution to the decolonization of archaeology by recasting colonialism within long-term Indigenous histories. Showcasing case studies from Africa, Australia, Mesoamerica, and North and South America, this edited volume highlights the work of archaeologists who study Indigenous peoples and histories on multiple scales. -- Book Jacket.